LARUNG DAN KEKUATAN PENGALAMAN YANG ADA DI DALAMNYA - Katrini, Yulia Esti (Majalah Transformatika, 2009)
Literatury work is created by the autherthrough contemplation, it means it is not created through blank idea. It can be said that literary work is created through yhe combination of knowledge of the author and his soul experience as the feflections of real human life novel "Larung" has a very strong and extra ordinary soul relation, especially it is because it is based on events of Indonesian historical life; the strength and weaknesses. All  of  the  events  are  composed in  the  story,  either  traditional  or modern one. The author clearly describes the real story estnetically that makes this literary work has high quality.   Keywords: Larung, Strength, soul